2014
DOI: 10.4172/2155-9899.1000257
|View full text |Cite
|
Sign up to set email alerts
|

MUC18 Differentially Regulates Pro-Inflammatory and Anti-Viral Responses in Human Airway Epithelial Cells

Abstract: Objective MUC18 or CD146, a transmembrane glycoprotein, is mainly expressed by endothelial cells and smooth muscle cells where it serves as a cell-cell adhesion molecule. We have found MUC18 up-regulation in airway epithelial cells of patients with asthma and chronic obstructive pulmonary disease (COPD). However, the function of MUC18 in airway epithelial cells remains unclear. In the present study, we tested the hypothesis that MUC18 exerts a pro-inflammatory function during stimulation with a viral mimic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…CD146 in CD4 + T cells is associated with Th17 differentiation in systemic sclerosis ( 9 ). CD146 is also associated with pulmonary infections, in which it promotes the adherence of bacteria or viruses to airway epithelial cells ( 11 14 ). Increased expression ofCD146 in gastric cancer leads to decreased expression of E-cadherin and increased expression of N-catenin and vimentin ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…CD146 in CD4 + T cells is associated with Th17 differentiation in systemic sclerosis ( 9 ). CD146 is also associated with pulmonary infections, in which it promotes the adherence of bacteria or viruses to airway epithelial cells ( 11 14 ). Increased expression ofCD146 in gastric cancer leads to decreased expression of E-cadherin and increased expression of N-catenin and vimentin ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A common characteristic of exacerbations of lung diseases is excessive inflammation, demonstrated by increases in neutrophils and IL-8, a chemoattractant of neutrophils. In our previous publication [ 3 ], we showed that MUC18 promotes IL-8 production in human airway epithelial cells. A study by Gern et al showed that IL-8 was rapidly induced after viral inoculation and contributed to neutrophil trafficking in the human upper airways [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…MUC18, also referred to as CD146 or melanoma cell adhesion molecule (MCAM), is a 113 kD transmembrane glycoprotein of the immunoglobulin superfamily [ 1 , 2 ]. MUC18 is comprised of an extracellular domain, a single transmembrane domain, and a short (63 amino acids) cytoplasmic tail [ 3 ]. It is upregulated in the airways of asthmatics and patients with chronic obstructive pulmonary disease (COPD), compared to healthy controls [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation